ANALISIS SISTEM AKUNTANSI PENERIMAAN KAS MASUK DALAM UPAYA PENINGKATAN EFEKTIVITAS PENGENDALIAN INTERNAL: Studi kasus pada Grage Business Hotel Yogyakarta - Firdarini, Khoirunnisa Cahya; Wijayanti, Erni (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2021)
This research aims to analyze cash receipt accounting system for room selling either in cash or on credit at Grage Business Hotel Yogyakarta. Based on Mulyadi theory, this research evaluate internal control effectivity of the hotel, especially for cash receipt system. The element have been evaluated are organizational structure, authority and administration procedure, and implementation of duties and obligation based on each person responsibilities. The data collection method used are observation, interview, and documentation. The results shows that implementation of internal control system as mention above at Grage Business Hotel Yogyakarta has not yet qualify Mulyadi theory criterias. The major problem there are not segregation of duties. Cash and sales function run by receptionist while accounting and administration function run by general cashier. The implication of this research is to improve internal control of cash receipt of the hotel.